Intervensi Group Cognitive and Behavioral Therapy (Group CBT) dalam Menangani Remaja dengan Ketergantungan Rokok - R.A. Innu Virgiani Agustya; Sugiarti A. Musabiq; Yudiana Ratna Sari (Fakultas Psikologi Universitas Pancasila, 2011)
Global Youth Tobacco Survey (GYTS) conducted in Indonesia in 2006 reported that 37.3 percent of students smoked, and three of ten students (30.9) started smoking at the age of younger than 10 years old. Therefore, it is important to develop an effective treatment for teen smokers to eliminate their smoking habit, and thus protect them from smoking negative impact as early as possible. Dealing with nicotine-addicted teens requires an approach that involves cognitive and behavioral aspects, and CBT is a method embracing both. This study observes the effectiveness of CBT group in the treatment of nicotine-addicted adolescent. CBT group method provides fundamental fact that it can develop adaptive responses of its members. In CBT group, participants can learn the principles of CBT in more active way. Individual capacity within a group to obtain an adaptive response often exceeds the ability of the individual itself in an individual setting (White & Freeman, 2000). The study reveals that the CBT group therapy is effective in reducing nicotine addiction of the four participants. The given therapy successfully decreases cigarette intake by 97.91% and lessen smoking motives by 44.30 percent. This therapy is also able to lower cigarette addiction to a very low level.